Science of floorball: a systematic review - Tervo T; Nordström A (Dove Medical Press, 2014)
Taru Tervo,1 Anna Nordström2 1Department of Surgical and Perioperative Sciences, Sports Medicine, Floorball Research and Development Center, Umeå School of Sport Sciences, 2Department of Surgical and Perioperative Sciences, Sports Medicine, Umeå School of Sport Sciences, Umeå University, Umeå, Sweden Background: The purpose of this study was to comprehensively review the scientific research on floorball at the competitive and recreational levels according to field of study. Methods: Full articles containing original data on floorball that had been published in English in peer-reviewed journals were considered for inclusion. Results: Of 75 articles screened, 19 were included in this systematic review. One article each was identified in the fields of sports management and sports psychology, and the remaining 17 articles were in the field of sports medicine. Injury epidemiology in floorball players was the most thoroughly examined topic of research. To date, no research has been performed on the incidence of floorball-related injury, or any aspect of the sport, in children and adolescents. Conclusion: Collaborative research among sports science disciplines is needed to identify strategies to reduce the incidence of injury and enhance the performance of licensed floorball players. Despite the increasing popularity of floorball in recent years, surprisingly little research has examined this sport. Keywords: floorball, unihockey, review